Current Ratio, Firm Size, and Return on Equity on Price Earnings Ratio with Dividend Payout Ratio as a Moderation and Firm Characteristic as Control Variable on the MNC 36 Index Period 2017-2021 - Renaldo, Nicholas; Rozalia, Dwi Kirtapati; Musa, Sulaiman; Wahid, Nabila; Cecilia (Journal of Applied Business and Technology, 2023)
This study aims to determine the effect of the Current Ratio, Company Size, Return on Equity, and Dividend Payout Ratio on the Price Earnings Ratio on the MNC36 index for the 2017-2021 period. The population and samples used in this study were to use the purposive sampling method which was selected based on specific criteria in accordance with the purpose of the study. Thus, the number of samples in this study was 77 companies. This study used secondary data. The analysis method in this study is multiple linear regression analysis using SPSS 22.0 and Smart PLS 4.0 software. The results of the research obtained are that DPR has a positive and significant effect on the Price Earnings Ratio. In contrast, the Current Ratio, Company Size, and Return on Equity do not have a significant effect on the Price Earnings Ratio.